SISTEM INFORMASI PERIZINAN BERBASIS WEBSITE DI ASRAMA MA’HAD ALY PUTRI - Ummul Khoirun Fitriyah; Nur Aida; Muftiyah Zakiyah; Nur Laili Mukarromah; Abdus Somad (Jurnal Riset Sistem Informasi, 2026)
The rapid development of information technology has encouraged Islamic boarding schools to modernize their administrative processes, including the management of student leave permits. At Asrama Ma'had Aly, the leave permit process is still conducted manually, causing various problems such as data loss, delays in approval, and difficulties in preparing reports. This study aims to design and develop a web-based leave permit information system to improve the effectiveness and efficiency of permit administration. The research employed a qualitative approach using field research and library research methods. Data were collected through interviews, observations, and documentation. The system development method used was the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance. The system was developed using PHP as the programming language and MySQL as the database management system. The resulting application enables students to submit permits online, allows administrators to verify and manage permit requests, and provides structured reporting features. The implementation of this system is expected to minimize data errors, reduce misuse of permits, and improve the overall efficiency of administrative services at Asrama Ma'had Aly